Faculty Senate, Minutes, March 24, 2016 - Faculty Senate, Valdosta State University (Valdosta State University, 2016)
Minutes March 24, 2016, 3:30 pm University Center Cypress Room | Peggy Moch - President; Mike Holt - Vice President/President Elect; Sudip Chakraborty - Secretary; Sean Lennon - Parliamentarian ; Michael Noll - Past President;
Electronic records processed at Valdosta State University Archives and Special Collections by Dallas A. Suttles (dasuttles@valdosta.edu) on 8/9/2016.
Keywords: Minutes (Records)